2015
DOI: 10.2147/amep.s72648
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of didactic grades to predict practical skills in an undergraduate dental college in Saudi Arabia

Abstract: ObjectivesThis longitudinal study was aimed to investigate the association between didactic grades and practical skills for dental students and whether didactic grades can reliability predict the dental students’ practical performance.Materials and methodsDidactic and practical grades for graduates from the Faculty of Dentistry, King Abdulaziz University, between the years 2009 and 2011 were collected. Four courses were selected: Dental Anatomy, Operative Dentistry, Prosthodontics, and Orthodontics. Pearson pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 15 publications
3
12
0
2
Order By: Relevance
“…Our findings are consistent also with the data of Zawawi et al who investigated four courses (Dental Anatomy, Prosthodontics, Operative Dentistry, and Orthodontics), although the positive correlations in the latter study were course specific (12) . Affifi et al study showed different results in which no correlation between the academic and the practical grades for the three courses (Dental Anatomy, Removable Prosthodontic Denture, Orthodontics) they used in their study (2) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent also with the data of Zawawi et al who investigated four courses (Dental Anatomy, Prosthodontics, Operative Dentistry, and Orthodontics), although the positive correlations in the latter study were course specific (12) . Affifi et al study showed different results in which no correlation between the academic and the practical grades for the three courses (Dental Anatomy, Removable Prosthodontic Denture, Orthodontics) they used in their study (2) .…”
Section: Discussionsupporting
confidence: 93%
“…It was suggested that the complex nature of modern dental practice requires broad range of skills that digital dexterity contributes only a small increment, or that technical dental procedures are completely trainable in the course of dental education (11) . Inspite of the positive correlation which was found, it was course specific (12) .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…19 Others involve more general measures of traits that could potentially capture dentistry-relevant skills, including spatial ability, 20 broad psychometric tests 21 and other predictors. 22 23 The majority of these approaches have had limited predictive value, with a call to use these as screening tools instead. 1 Unfortunately, such approaches are ethically problematic if there is no empirical evidence to show a relationship between the measure and the ability to practice dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…Investigators in more recent years have concentrated on the development of marking systems centered on specific criteria and checklists as an alternative to the glance and grade method commonly used in clinical sessions, in order to improve rater performance, but the results have been vague ( 7 ). Some researchers found that development of an analytical approach using detailed checklists improved examiner reliability ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%